Effects of interleukin-1 antagonism on cortisol levels in individuals with obesity: a randomized clinical trial - Fahim Ebrahimi; Sandrine A Urwyler; Philipp Schuetz; Beat Mueller; Luca Bernasconi; Peter Neyer; Marc Y Donath; Mirjam Christ-Crain (Endocrine Connections, 2019)
Background: Anti-inflammatory treatment with interleukin-1 (IL-1) antagonism decreases both cortisol and adrenocorticotropin hormone (ACTH) levels in individuals with obesity in short term. However, it remains unknown whether these effects persist upon prolonged treatment. Methods: In this double-blind, parallel-group trial involving patients with features of the metabolic syndrome, 33 patients were randomly assigned to receive 100 mg of anakinra (recombinant human IL-1 receptor antagonist) subcutaneously twice-daily and 34 patients to receive placebo for 4 weeks. For this analysis, change in cortisol and ACTH levels from baseline to 4 weeks were predefined end points of the trial. Results: The mean age was 54 years, baseline cortisol levels were 314 nmol/L (IQR 241–385) and C-reactive protein (CRP) levels were 3.4 mg/L (IQR 1.7–4.8). Treatment with anakinra led to a significant decrease in cortisol levels a t day 1 when compared to placebo with an adjusted between-group difference of 28 nmol/L (95% CI, −7 to −43; P = 0.03). After 4 weeks, the cortisol-lowering effect of anakinra was attenuated and overall was statistically not significant (P = 0.72). Injection-site reactions occurred in 21 patients receiving anakinra and were associated with higher CRP and cortisol levels. Conclusions: IL-1 antagonism decreases cortisol levels in male patients with obesity and chronic low-grade inflammation on the short term. After prolonged treatment, this effect is attenuated, probably due to injection-site reactions (ClinicalTrials.gov, NCT02672592).